Merchants of the right : gun sellers and the crisis of American democracy - Carlson, Jennifer (Princeton University Press, 2023)
"Gun sales have not just surged in the past two years-they have skyrocketed, breaking all-time records from March to July 2020. In this book, Jennifer Carlson examines the three dire crises in the United States in 2020-the pandemic, police murders and subsequent uprisings for racial justice, and the 2020 elections-to examine how Americans have turned to a well-worn tool of security in American life: the gun. While the notion that Americans would turn to guns for safety and security is hardly new, the utility of guns amidst the collective crises of 2020 is not so straight-forward. Carlson documents how people positioned at the frontlines of gun culture and conservative politics-namely, gun sellers-navigate the mismatch between guns as an esteemed tool of safety and security in the US context and the real-life crises that guns are deemed capable of solving, not least because many Americans believe they have no other option. Drawing on in-depth interviews with over 50 gun sellers across the United States and pro-gun media, as well as historical and legal accounts, Carlson explores the politics of gun rights in 2020 as a window into the broader challenges currently faced by American democracy. She begins with the National Rifle Association's transformation into a political organization in the second half of the 20th century and identifies three tools that were essential to that transformation: armed individualism, conspiracism, and partisanship. Focusing on each tool in subsequent chapters, she argues that gun owners, gun sellers, and gun rights advocates have used these tools to not just defend gun rights but also to understand and engage the political tensions they confront in their everyday lives. In doing so, she illuminates the underlying processes by which conservative Americans have deepened contempt for liberal democracy, and with what consequences"-- Provided by publisher.
Keywords: Firearms ownership -- Political aspects -- United States.; Democracy -- United States.; Conservatism -- United States.; Right-wing extremists -- United States.; Polarization (Social sciences) -- United States.; Armes à feu -- Possession -- Aspect politique -- États-Unis.; Conservatisme -- États-Unis.; Extrémistes de droite -- États-Unis.; Polarisation collective -- États-Unis.; SOCIAL SCIENCE / Violence in Society.; SOCIAL SCIENCE / Sociology / General.; Conservatism; Democracy; Polarization (Social sciences); Right-wing extremists; United States; Electronic books.